The worst-case scenario survival handbook : junior edition - Borgenicht, David; Epstein, Robin, 1972-; Gonzales, Chuck (San Francisco : Chronicle Books, 2007)
Provides advice for kids on how to deal with a variety of situations, such as getting a bad report card, outsmarting a prankster, surviving a canine encounter, increasing an allowance, and more.
Survival skills at home -- Survival skills at school -- Survival skills for your social life -- Survival skills for the outdoors.
5.9
3-6
3-6
Keywords: Children -- Humor -- Juvenile literature; Social skills in children -- Juvenile literature; Socialization -- Juvenile literature; Social skills; Socialization; Wit and humor; Social skills; Socialization; Wit and humor